The Construction Industry and Modernization-Applying Change Concepts (Global Journals of Research in Engineering, 2020)
Globalization has fully taken its course in no other sector more apparent than in the rapidly growing construction industry The industry is being forced to change at an unprecedented pace Nigeria and other developing countries are not exempted as they witness a fast-growing rate of construction activities also The industry must adapt to a global trend and a sense of camaraderie to meet the huge demands reduce risks involved thus safeguarding quality and profitability Change is an enormously complex issue but the industry must take cognizance of the change demand to gain competitive advantages The aim of this study is to examine the effect of change application on the modernization of the construction industry This paper presents the results of a literature review carried out on change application in modernization of construction industry It examines the issues that will cause change reviews the available literature to find how change can be managed and controlled and develops a model for guiding change programmes in the construction industry Interviews and questionnaire surveys were adopted tools in getting data and analyzed to achieve the research aim
Keywords: change; construction industry; globalization; management and modernization